WhatsApp and Wellness: Exploring the Motivations and Challenges in Health Literacy and Health Information Seeking Among African Immigrants - Sunday Olaniran (International Journal of Management, Knowledge and Learning)
Purpose: The purpose of this study is to investigate health information seeking behavior of African Immigrants in Vancouver, British Columbia, Canada.